Design and Fabrication of Customized Ais Kacang Vending Machine - Muchamad Oktaviandri; D.K. A V Paramasivam (Faculty of Engineering and Technology, Sampoerna University, 2020)
Nowadays, machines play a critical role as those machines are broadly utilized in various subjects. The contribution of machines is swiftly growing day by day as they are starting to replace humans in everyday tasks. The machine is also used for the food and beverage industry to deliver the products easily and conveniently to customers. This paper focuses on the design and fabrication of the customized Ais Kacang vending machine for canteen, cafeteria and restaurant usage. There were five designs made and one best conceptual design was selected by using a ranking method. In addition, this paper explains the stress and strain analyses of the internal frame of the vending machine. The Ais Kacang vending machine has been undergone two tests, the geometrical and final product tests. The selected machine was able to produce a plate of Ais Kacang in 66 seconds using auto mode. However, the time needed to produce a plate of Ais Kacang in manual mode depended on the user.